A transcriptional landscape underlying sugar import for grain set in maize. (25th February 2022) - Shen, Si; Ma, Si; Chen, Xian‐Min; Yi, Fei; Li, Bin‐Bin; Liang, Xiao‐Gui; Liao, Sheng‐Jin; Gao, Li‐Hong; Zhou, Shun‐Li; Ruan, Yong‐Ling
SUMMARY: Developing seed depends on sugar supply for its growth and yield formation. Maize ( Zea mays L.) produces the largest grains among cereals. However, there is a lack of holistic understanding of the transcriptional landscape of genes controlling sucrose transport to, and utilization within, maize grains. By performing in‐depth data mining of spatio‐temporal transcriptomes coupled with histological and heterologous functional analyses, we identified transporter genes specifically expressed in the maternal–filial interface, including (i) ZmSWEET11/13b in the placento‐chalazal zone, where sucrose is exported into the apoplasmic space, and (ii) ZmSTP3, ZmSWEET3a/4c (monosaccharide transporters), ZmSUT1, and ZmSWEET11/13a (sucrose transporters) in the basal endosperm transfer cells for retrieval of apoplasmic sucrose or hexoses after hydrolysis by extracellular invertase. In the embryo and its surrounding regions, an embryo‐localized ZmSUT4 and a cohort of ZmSWEETs were specifically expressed. Interestingly, drought repressed those ZmSWEETs likely exporting sucrose but enhanced the expression of most transporter genes for uptake of apoplasmic sugars. Importantly, this drought‐induced fluctuation in gene expression was largely attenuated by an increased C supply via controlled pollination, indicating that the altered gene expression is conditioned by C availability. Based on the analyses above, we proposed a holistic model on the spatio‐temporal expression of genes that likely govern sugar transport and utilization across maize maternal and endosperm and embryo tissues during the critical stage of grain set. Collectively, the findings represent an advancement towards a holistic understanding of the transcriptional landscape underlying post‐phloem sugar transport in maize grain and indicate that the drought‐induced changes in gene expression are attributable to low C status. Significance Statement: Although maize ( Zea mays L.) produces the largest grain among cereals through a small 'gateway' for assimilates, indicating a strong sink capacity, there is a lack of holistic understanding of the molecular basis underlying sugar import into the grains. Here, we uncovered a cohort of key genes controlling sugar delivery to the endosperm and embryo and further found that drought repressed those genes exporting sucrose into the apoplasmic space but enhanced those genes involved in uptake of sugars by the filial tissues.